Class Management in Improving Learning Performance in The Classroom - Mujiono Mujiono (AT-TURATS, 2021)
This research is motivated by the implementation of classroom management by interesting teachers, namely by changing the student seating model at each meeting. However, the media used by teachers is not adequate in delivering teacher material such as monotony only dictates the material. And there are some students who do not want to play an active role in learning, lazing in class, and talking to their compatriots when the teacher is explaining.The purpose of this study is to know about: 1) How teachers organize Classroom VIII at Al-Khairat Kubu Raya Junior High School 2020/2021. 2) The management of Class VIII that teachers do in the learning process at Al-Khairat Kubu Raya Junior High School in the 2020/2021 School Year. 3) The spirit of learning of Class VIII students after the management of the class is well implemented at Al-Khairat Kubu Raya Junior High School in the 2020/2021 School Year.The data sources in this study are teachers of Islamic Religious Education subjects as the main source, and supporting data sources, namely students of class VIII of Al-Khairat Junior High School who were appointed. This form of research uses a qualitatively de-decriminal approach. Using data collection tool techniques: observation, interviews and documentation. Data analysis techniques: data reduction, presentation of data, and drawing conclusions or verifications. While the data validity test technique used is: triangulation and member chek. The results of this study can be concluded: 1) The arrangement of classroom VIII at Al-Khairat Kubu Raya Junior High School in the 2020/2021 School Year  has been  done by the teacher    by:    directing  students  to organize the study room before learning begins and preparing learning facilities. In addition, the teacher changes the model of student seating at each meeting in a way before ending the teacher's lesson    shakes the  seating  model  that  will be used at the next meeting, the teacher also guides students to maintain the cleanliness and beauty of the class. 2) The management of class VIII that teachers do in the learning process at Al-Khairat Kubu Raya Junior High School of the Year.  Lesson 2020/2021 is that teachers use different methods at  each  meeting  and the methods  used  are  adjusted to  the  material to be taught. In addition to using different methods, teachers also use learning media even though the media used by teachers is only sober. 3) The spirit of learning of class VIII students after the implementation of class management is carried out well at Al-Khairat Kubu Raya Junior High School in the 2020/2021 School Year, which is after the teacher manages the class and provides  motivation  to  students so that students  are  passionate  in  learning   By giving gifts to the most active students, there are still some students who are passionate and not passionate in learning this is because students feel the teacher's way of teaching is  boring.